2007
DOI: 10.1159/000103198
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and immune characteristics of aging in avian species

Abstract: Avian species show a remarkable diversity in lifespan. The differing lifespan patterns are found across a number of birds, in spite of higher body temperature and apparent increased metabolic rate. These characteristics make study of age-related changes of great interest, especially for understanding the biology of aging associated with surprisingly long lifespan in some birds. Our studies have focused on a short-lived avian model, the Japanese quail in order to describe reproductive aging and the neuroendocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…The brain content of GnRH decreases in both males and females with senescence; interestingly in senescent males, the decrease in GnRH is seen in both the POA and ME, while in senescent females the decline is seen in the ME but not the POA. These findings are consistent with the observation that neuronal cell number changes little with aging in females but in males, cell number decreases with aging (81). In addition, the observations of Dellovade et al (31) indicate that individual male quail reproductively age at different rates and that this rate reflects the aging of the underlying neuroendocrine system that regulates reproductive behaviors.…”
Section: Birdssupporting
confidence: 83%
“…The brain content of GnRH decreases in both males and females with senescence; interestingly in senescent males, the decrease in GnRH is seen in both the POA and ME, while in senescent females the decline is seen in the ME but not the POA. These findings are consistent with the observation that neuronal cell number changes little with aging in females but in males, cell number decreases with aging (81). In addition, the observations of Dellovade et al (31) indicate that individual male quail reproductively age at different rates and that this rate reflects the aging of the underlying neuroendocrine system that regulates reproductive behaviors.…”
Section: Birdssupporting
confidence: 83%
“…We have concluded that differences in spleen mass between wild and domestic mink, and between feral domestic mink and domestic mink on farms are the result of differences in the prevalence and abundance of parasites and pathogens. Nonetheless, spleen size can be affected by other factors, including age (Ottinger & Lavoie, ; Cowan et al ., ), stress (McEwan et al ., ), and season (Silverin et al ., ). We argue that age is unlikely to be a factor because even if wild and domestic mink vary in age, age differences are unlikely to explain differences in spleen mass between domestic and feral mink, given that feral mink had escaped from mink farms.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations are also observed in non-mammalian species, with comparison of short- and long-lived species such as in birds ( Ogburn et al, 2001 ). Furthermore, short-lived species show many age-related declines in neural and endocrine systems and increased incidence of cancer ( Gorham and Ottinger, 1986 ; Ottinger et al, 2004 ; Ottinger and Lavoie, 2007 ; Ottinger, 2007 ; Johnson and Giles, 2013 ). As such, these comparative studies offer significant insights into conserved mechanisms occurring throughout vertebrates during the aging process ( National Academy of Sciences, 2014 ; Niedernhofer et al, 2017 ).…”
Section: Aging Biology and Environmental Toxicantsmentioning
confidence: 99%